1998
DOI: 10.1507/endocrj.45.785
|View full text |Cite
|
Sign up to set email alerts
|

A Progesterone Antagonist Cannot Prevent Fetal Survival if the Uterine Horn is Incised.

Abstract: Abstract. The fetuses released into the abdominal cavity by uterine incision escape from most physical influences of the uterus. This study examined whether these fetuses require progesterone actions for survival during late pregnancy in rats. A longitudinal incision in one uterine horn (with the other horn intact) together with bilateral ovariectomy (OVX), removal of the main progesterone-production sites, or sham OVX, were performed on day 18 of pregnancy. Thereafter the rats were given daily subcutaneous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Since treatment with E 2 restored the changes in uterine physical properties caused by the Fad treatment and prevented fetal injuries, it is possible that the specific role of estrogen during the second half of pregnancy is to develop the uterine tissue framework needed to maintain normal fetal growth in rats. The importance of the uterine physical environment to fetal survival during late pregnancy has been demonstrated in ovariectomized rats and rats treated with a progesterone antagonist (Tamada & Mori 1995, Tamada et al 1998. Although high doses of androgens have estrogenic effects and maintain successful pregnancy in the ovariectomized progesterone-treated rats (Hosoda et al 1984), increased production of androgen in the Fad-treated rats could not have overcome the influences of the estrogen deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Since treatment with E 2 restored the changes in uterine physical properties caused by the Fad treatment and prevented fetal injuries, it is possible that the specific role of estrogen during the second half of pregnancy is to develop the uterine tissue framework needed to maintain normal fetal growth in rats. The importance of the uterine physical environment to fetal survival during late pregnancy has been demonstrated in ovariectomized rats and rats treated with a progesterone antagonist (Tamada & Mori 1995, Tamada et al 1998. Although high doses of androgens have estrogenic effects and maintain successful pregnancy in the ovariectomized progesterone-treated rats (Hosoda et al 1984), increased production of androgen in the Fad-treated rats could not have overcome the influences of the estrogen deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The E 1 S concentration in the blood of the smaller littermate group was significantly higher than those in the other groups, as was the birth and placental weight. Tamada et al . (1998) reported that ovariectomy increased placental weight in the incised uterine horn of pregnant rats.…”
Section: Discussionmentioning
confidence: 99%
“…ovariectomy and/or treatment with anti-P RU 486 in late pregnant rats, indicating that indispensable actions of ovarian hormones for fetal survival are directed to the physical properties of uteri in late pregnancy [10,11]. Namely, well-known action of P for inhibition of uterine smooth muscle activity through its receptor signaling [12] and enlargement of uterine tissue framework for rapidly growing fetuses by P plus estrogen could be critical for maintenance of late pregnancy.…”
mentioning
confidence: 99%